1996
DOI: 10.1046/j.1365-2133.1996.19754.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prognosis of subungual melanoma in 34 Japanese patients

Abstract: The incidence of malignant melanoma is much lower in the Japanese than in caucasians. However, amongst the various types of malignant melanoma, the subungual and periungual sites are commonly found in the Japanese. One hundred and fifty-one cases of cutaneous malignant melanoma were seen over a 25-year period at our hospital. We found that, in 34 patients (23%), the subungual region was involved, a high frequency for one institution. We have analysed these patients and looked at their treatment. The finger nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
3
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 16 publications
5
60
3
4
Order By: Relevance
“…Finally, melanomas considered to be nonphotoinduced (NPIM) include (i) melanomas located on nonphotoexposed sites (sun-protected skin areas or mucous localisations) and (ii) subungual and acral lentiginous melanomas that are considered to be particular subtypes of melanoma, because, in contrast to other subtypes, ultraviolet irradiation is not a major factor in their development (Kato et al, 1996;Saida, 2001), thus suggesting genetic factors in their onset.…”
mentioning
confidence: 99%
“…Finally, melanomas considered to be nonphotoinduced (NPIM) include (i) melanomas located on nonphotoexposed sites (sun-protected skin areas or mucous localisations) and (ii) subungual and acral lentiginous melanomas that are considered to be particular subtypes of melanoma, because, in contrast to other subtypes, ultraviolet irradiation is not a major factor in their development (Kato et al, 1996;Saida, 2001), thus suggesting genetic factors in their onset.…”
mentioning
confidence: 99%
“…The pigmentation of the surrounding nail tissue, called Hutchinson's sign, paired with nail lifting is indicative of melanoma [22]. The continued linear growth of dark bands subungually, or longitudinal melanonychia, is indicative of melanoma, especially if it is greater than 3 mm wide or wide at the base with distal tapering [23,37]. Some studies report an increased risk of melanoma secondary to trauma, however, the Cohen study reported trauma as an inciting factor in only 10 % of patients [11].…”
Section: Malignant Melanomamentioning
confidence: 99%
“…The incidence of amelanotic melanoma in all melanomas is low, although the subungual region seems to be an area of predilection for amelanotic melanoma in 15 to 25% of cases 4,6 . The lack of pigmentation causes the clinical appearance to be nonspecific for melanoma.…”
Section: Case Reportmentioning
confidence: 99%
“…Approximately 15 to 25% of cases of subungual melanoma are amelanotic. The lack of pigmentation of the lesion may cause misdiagnosis and aggravate its poor prognosis [4][5][6] . We herein report on a case of amelanotic subungual melanoma extended to the adjacent skin in a 36-year-old Korean woman.…”
Section: Introductionmentioning
confidence: 99%